2019
DOI: 10.1155/2019/1850141
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of High-Frequency Deep Sclerotomy in Treatment of Chronic Open-Angle Glaucoma Patients

Abstract: Purpose Highlights the high-frequency deep sclerotomy as a competing ab interno surgery in open-angle glaucoma patients and evaluates the efficacy of high-frequency deep sclerotomy in lowering IOP of chronic open-angle glaucoma patients, in addition to the evaluation of the safety of the procedure on the corneal endothelium. Design A prospective study. It was performed in the Research Institute of Ophthalmology, Cairo. Participants 43 eyes were enrolled for the study. All eyes were diagnosed with chronic open-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…6 Recently, we have discovered that this instrument may also be used for the creation of surgical PIs, provided that the machine is set to "high frequency deep sclerotomy," a setting with a different waveform that is more suited for cutting dense tissue. 7,8 Because the device simultaneously cauterizes as it cuts, the risk for intraoperative hemorrhage is low. Further, the handpiece is intuitive to use and reusable, which may be a relevant consideration in many surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recently, we have discovered that this instrument may also be used for the creation of surgical PIs, provided that the machine is set to "high frequency deep sclerotomy," a setting with a different waveform that is more suited for cutting dense tissue. 7,8 Because the device simultaneously cauterizes as it cuts, the risk for intraoperative hemorrhage is low. Further, the handpiece is intuitive to use and reusable, which may be a relevant consideration in many surgical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the new nomenclature was to describe the procedure more precisely. Regarding the procedure, there were no differences between STT ab interno and HFDS [17][18][19][20].…”
Section: Introductionmentioning
confidence: 85%
“…High-frequency deep sclerotomy (HFDS), originally known as sclerothalamotomy ab interno (STT ab interno), aims to reduce IOP by creating microincisions in the sclera using high-frequency electric current, thereby enhancing uveoscleral outflow [ 32 , 33 ]. The HFDS procedure involves the placement of a specialized diathermic probe (Oertli Instrumente) equipped with a high-frequency generator into the suprachoroidal space, creating multiple small incisions in the sclera.…”
Section: Devices Procedures and Surgical Techniquesmentioning
confidence: 99%
“…Initial studies investigating the use of HFDS in glaucoma management have shown encouraging results, with significant reductions in IOP and a favorable safety profile [ 32 , 33 , 35 ]. In addition, HDFS can be combined with cataract surgery while avoiding the risk of implant-related complications and has a relatively short learning curve for surgeons already experienced in glaucoma surgery.…”
Section: Devices Procedures and Surgical Techniquesmentioning
confidence: 99%